PATHOMORPHOLOGICAL CHANGES IN RABBIT ORGANISM CAUSED BY EXPERIMENTAL STAPHYLOCOCCOSIS - Tul, O. I. (Scientific Progress & Innovations, 2020)
In infectious pathology of animals, the etiological role of staphylococci has increased significantly in re-cent years. These microorganisms are able to infect any organs and tissues of the body. The most common are lesions of the skin and subcutaneous tissue, abscesses, sepsis and septicopyemia. Rabbits are very sus-ceptible to staphylococcal infections and therefore they are widely used as laboratory animals to determine the pathogenicity of causative agent. The aim of the study was to determine pathomorphological changes in rabbit organism during experimental reproduction of staphylococcosis using the suspension of Staphylococ-cus epidermidis pure culture isolated from sand lizard. Eight clinically healthy rabbits from Poltava private farm were used in scientific studies. The suspension of Staphylococcus epidermidis pure culture isolated from sand lizard was used to infect laboratory animals. As a result of infecting the following pathological changes were observed in animals’ organism: hyperemia, protein hepaptosis, nephrosis, myocardosis, hem-orrhagic diathesis of heart membranes, tracheal and large bronchi mucous membrane, and serous mem-brane of the intestinal wall. Catarrhal gastroenteritis, moderate intestinal meteorism, areas of focal serous pneumonia, and dermatitis were registered. The histological examination of the liver revealed the enlarge-ment of the lumens of capillary sinusoids, the edema of the wall of medium-sized blood vessels with vacuoli-zation of endotheliocytes, and the formation of perivascular infiltrates from granulocytes. Foci of serous pneumonia, catarrhal bronchitis, perivascular edema were observed in the lungs. The infiltration of the walls of alveoli, bronchi and peribronchial connective tissue with granulocytes, edema of the stroma with the formation of transudate or serous exudate with admixture of neutrophils and eosinophils were registered. In the kidneys, vessels of various calibers were blood-filled, edema and foci of necrosis of the stroma of the cor-tical zone were observed. Focal hyperemia, sub-capsular hemorrhages, edema of red and white pulp, foci of mucoid swelling of the capsule and trabeculae were found in the spleen and lymphatic nodes. The obtained research results indicate that rabbit organism during experimental staphylococcosis was intoxicated by the pathogen metabolism products, which led to severe pathological changes in parenchymal organs.